Pelatihan Pengelolaan Profesional Etiket bagi Karyawan Rumah Makan Guna Meningkatkan Efisiensi dan Efektivitas Layanan - Didik Hariyadi Raharjo; Fenti Sofiani; Wiwin Windihastuty; Reni Hariyani (Jurnal Relawan dan Pengabdian Masyarakat REDI, 2024)
Salmontei & Station Coffee restaurant is a restaurant with an old Japanese theme which aims to create a comfortable place to eat and rest for visitors. This restaurant is located on Jl. K.H. Syafi'i Hadzami 8B, North Kebayoran Lama, South Jakarta. Currently, Salmontei Restaurant & Station Coffee is committed to developing its business and also providing the best service for all customers. However, this restaurant has various problems faced, including: a lack of understanding of professional etiquette in serving restaurant customers. For this reason, this training is aimed at: increasing self-confidence and ability to manage service quality for all Salmontei Restaurant & Station Coffee employees. This PKM activity will be carried out face to face on Monday, November 28 2022, at the Salmontei & Station Coffee restaurant starting at 09.00-11.00 WIB. This PKM activity is carried out using 3 methods including: lectures to deliver the material; discussion, role play, and giving questionnaires. The results of this activity show that the participants can increase their understanding and mastery of professional etiquette which will also increase their understanding of their abilities in serving guests at the Salmontei & Station Coffee restaurant.